Synthesis and Antifungal Activity of Fmoc-Protected 1,2,4-Triazolyl-α-Amino Acids and Their Dipeptides Against Aspergillus Species - Tatevik Sargsyan; Lala Stepanyan; Henrik Panosyan; Heghine Hakobyan; Monika Israyelyan; Avetis Tsaturyan; Nelli Hovhannisyan; Caterina Vicidomini; Anna Mkrtchyan; Ashot Saghyan; Giovanni N. Roviello (Biomolecules)
In recent years, fungal infections have emerged as a significant health concern across veterinary species, especially in livestock such as cattle, where fungal diseases can result in considerable economic losses, as well as in humans. In particular, Aspergillus species, notably Aspergillus flavus and Aspergillus versicolor, are opportunistic pathogens that pose a threat to both animals and humans. This study focuses on the synthesis and antifungal evaluation of novel 9-fluorenylmethoxycarbonyl (Fmoc)-protected 1,2,4-triazolyl-α-amino acids and their dipeptides, designed to combat fungal pathogens. More in detail, we evaluated their antifungal activity against various species, including Aspergillus versicolor (ATCC 12134) and Aspergillus flavus (ATCC 10567). The results indicated that dipeptide 7a exhibited promising antifungal activity against Aspergillus versicolor with an IC50 value of 169.94 µM, demonstrating greater potency than fluconazole, a standard treatment for fungal infections, which showed an IC50 of 254.01 µM. Notably, dipeptide 7a showed slightly enhanced antifungal efficacy compared to fluconazole also in Aspergillus flavus (IC50 176.69 µM vs. 184.64 µM), suggesting that this dipeptide might be more potent even against this strain. Remarkably, 3a and 7a are also more potent than fluconazole against A. candidus 10711. On the other hand, the protected amino acid 3a demonstrated consistent inhibition across all tested Aspergillus strains, but with an IC50 value of 267.86 µM for Aspergillus flavus, it was less potent than fluconazole (IC50 184.64 µM), still showing some potential as a good antifungal molecule. Overall, our findings indicate that the synthesized 1,2,4-triazolyl derivatives 3a and 7a hold significant promise as potential antifungal agents in treating Aspergillus-induced diseases in cattle, as well as for broader applications in human health. Our mechanistic studies based on molecular docking revealed that compounds 3a and 7a bind to the same region of the sterol 14-α demethylase as fluconazole. Given the rising concerns about antifungal resistance, these amino acid derivatives, with their unique bioactive structures, could serve as a novel class of therapeutic agents. Further research into their in vivo efficacy and safety profiles is warranted to fully realize their potential as antifungal drugs in clinical and agricultural settings.